2021
DOI: 10.3390/su13179871
|View full text |Cite
|
Sign up to set email alerts
|

Economic Fluctuation, Local Government Bond Risk and Risk-Taking of City Commercial Banks

Abstract: Countercyclical fiscal regulation can mitigate economic risk, but this is bound to increase the scale of local government debt during an economic downturn, and then spread risk to the banking sector, forming potential financial instability factors. We extracted the three most important variables in this process: economic fluctuation, local debt risk and bank risk-taking to build an econometric model and found that: (1) both economic fluctuations and local government bond risks have a significant impact on bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Following the 2007 U.S. subprime crisis, economists extensively discussed the relationship between credit fluctuations in non-financial corporations and households and economic growth. However, the related research is still an ongoing and open discussion, far from reaching a consensus [26][27][28][29][30][31]. Nonetheless, there has been some consensus at the empirical level regarding the adverse effects of rapid credit growth on the economy [32][33][34][35].…”
Section: Impact Of Credit Fluctuations On Economic Growthmentioning
confidence: 99%
“…Following the 2007 U.S. subprime crisis, economists extensively discussed the relationship between credit fluctuations in non-financial corporations and households and economic growth. However, the related research is still an ongoing and open discussion, far from reaching a consensus [26][27][28][29][30][31]. Nonetheless, there has been some consensus at the empirical level regarding the adverse effects of rapid credit growth on the economy [32][33][34][35].…”
Section: Impact Of Credit Fluctuations On Economic Growthmentioning
confidence: 99%
“…Local governments require more money due to China's economy's continued growth to promote infrastructure development and protect livelihood initiatives, while local revenues can hardly make up for the huge shortage of funds. Therefore, most local governments need to obtain funds by borrowing, which results in local government debt [1][2][3]. By investing debt funds in regional infrastructure construction, local governments can improve regional public infrastructure and enhance residents' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, through the analysis of the current situation of monitoring of sports training process in China, it is found that there are still many problems: (1) Sports teams or coaches conduct scientific monitoring of the sports training process. is selection is largely spontaneous [20][21][22][23][24]. e selection did not form a fixed mechanism with a certain department head.…”
Section: Introductionmentioning
confidence: 99%